How do gut microbes influence mental health?. Issue 3 (16th May 2022) - Dinan, Timothy G
Abstract : It is now clear that gut microbes influence brain function. Poor diet leads to an altered microbiota. Accumulating evidence supports the view that gut dysbiosis is associated with depression and that treatments targeting the microbiota can be beneficial to people's mental health.